TRAINING ON THE USE OF ARTIFICIAL INTELLIGENCE (AI) TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS’ WRITING SKILLS IN THE DIGITAL ERA - Mawardi, Mawardi; Rifki, Rifki; Helmiyadi, Helmiyadi; Fauzar, Fauzar; Farras Chanira, Siti; Khair, Nisaul; Ramadhana, Muhammad (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2025)
This study investigates the effectiveness of an AI-assisted writing training program in improving junior high school students’ writing skills in a rural context. The program was conducted at SMP Negeri 2 Matangkuli, North Aceh, involving 40 students from Grades VII to IX over two months (October–November 2025). A quasi-experimental one-group pretest. Posttest design was applied. Students participated in structured writing workshops integrating AI tools such as Grammarly, QuillBot, and ChatGPT. The results showed a significant improvement in students’ writing performance, with the mean score increasing from 62.45 in the pre-test to 74.10 in the post-test (p 0.05). The most notable progress was observed in grammar and vocabulary use. In addition, students demonstrated higher engagement, confidence, and digital literacy in using AI responsibly. The findings indicate that AI-assisted writing instruction can effectively enhance EFL writing skills and support digital learning in rural schools when implemented with proper guidance and supervision.